ChemInform Abstract: An Overview of Zn‐Catalyzed Enantioselective Aldol Type C—C Bond Formation. Issue 37 (September 2015) - Thankachan, Amrutha P.; Asha, S.; Sindhu, K. S.; Anilkumar, Gopinathan
Abstract Review: [76 refs.